2014
DOI: 10.1002/pro.2558
|View full text |Cite
|
Sign up to set email alerts
|

Distinct circular dichroism spectroscopic signatures of polyproline II and unordered secondary structures: Applications in secondary structure analyses

Abstract: Circular dichroism (CD) spectroscopy is a valuable method for defining canonical secondary structure contents of proteins based on empirically-defined spectroscopic signatures derived from proteins with known three-dimensional structures. Many proteins identified as being "Intrinsically Disordered Proteins" have a significant amount of their structure that is neither sheet, helix, nor turn; this type of structure is often classified by CD as "other", "random coil", "unordered", or "disordered". However the "ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
183
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(204 citation statements)
references
References 33 publications
18
183
1
2
Order By: Relevance
“…This collagen fibril spectrum is distinct from a soluble triple helix and is similar in spectral shape to the polyproline II structure but has a much larger magnitude (Fig. S8) (52,53). This signal is strongly correlated with other measurements of fibrillogenesis, such as rheology and light scattering, and is evident for a number of type-I collagens from diverse source tissues and species.…”
Section: Discussionmentioning
confidence: 92%
“…This collagen fibril spectrum is distinct from a soluble triple helix and is similar in spectral shape to the polyproline II structure but has a much larger magnitude (Fig. S8) (52,53). This signal is strongly correlated with other measurements of fibrillogenesis, such as rheology and light scattering, and is evident for a number of type-I collagens from diverse source tissues and species.…”
Section: Discussionmentioning
confidence: 92%
“…[41,76] A consensus has emerged in the past decade that "disordered" proteins are in fact often dominated by residues that temporally adopt extended (or semi-extended) PII conformations, [39] notably for short peptides. [77,78] For instance NMR studies demonstrated that a 7-residue poly-Ala in aqueous solution adopted a PPII conformation, [40] and similar results were obtained for the penta-peptide GGAGG.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we continued all further analyses in 50 mM phosphate buffer pH 7.2, as it is close to physiological conditions. We examined the effect of detergent concentration on the far-UV CD spectra of TM2, using LDAO (4,10,20,40, and 100 mM) and DPC (5,10,20,30, and 50 mM). In LDAO samples ( Figure 5, top left panel), we observe an increase in the overall ellipticity, which is accompanied by a red shift in the negative maximum from 200 to 204 nm, as the LDAO concentration increases.…”
Section: Structure Of Tm2 Is Independent Of Ph and Micelle Concentratmentioning
confidence: 99%
“…12 It is broadly accepted that PPII structures are observed in poly-L-Pro, poly-L-Glu, poly-L-Lys, and the collagen sequence. 4,[13][14][15] However, segments that adopt PPII-like structures have been observed in short polypeptides and proteins. [16][17][18][19] PPII-like segments with a minimum of length two residues and a maximum of 14 residues has been observed to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation